Multidrug-resistant Pseudomonas aeruginosa from sputum of patients with cystic fibrosis demonstrates a high rate of susceptibility to ceftazidime–avibactam - Atkin, Stan D (Infect Drug Resist, 2018)
PURPOSE: Ceftazidime–avibactam is a novel antimicrobial combining a third-generation cephalosporin with a non-β-lactam β-lactamase inhibitor that was recently approved to treat Gram-negative hospital- and ventilator-acquired pneumonia. The use of ceftazidime–avibactam to treat Pseudomonas aeruginosa respiratory infections in patients with cystic fibrosis (CF) has not been evaluated. In this study, we assessed the ceftazidime–avibactam susceptibility of multidrug-resistant (MDR) P. aeruginosa sputum isolates from adults with CF. METHODS: Sputum was collected from individuals with CF, aged ≥18 years, known to be colonized with MDR P. aeruginosa, and tested for susceptibility to 11 different antipseudomonal antimicrobial agents. Isolates were included in the analysis if they were resistant to both ceftazidime and at least one agent in ≥3 different antimicrobial categories routinely used to treat P. aeruginosa. Subject demographics and clinical characteristics were collected. Ceftazidime–avibactam-resistant isolates were screened for the presence of β-lactam-resistant mechanisms. RESULTS: Thirty-two P. aeruginosa isolates were analyzed, of which 23 isolates were sensitive to ceftazidime–avibactam (71.9%). Ten of the isolates were mucoid and 22 isolates were nonmucoid, both demonstrating >70% susceptibility to ceftazidime–avibactam. The most notable difference in the subjects with resistant strains was an older age and lower body mass index (BMI). Ceftazidime–avibactam-resistant strains showed elevated AmpC expression in >60% of the strains and loss of OprD detection in >70% of the strains. CONCLUSION: Ceftazidime–avibactam demonstrated a significant in vitro activity against highly resistant P. aeruginosa sputum isolates from individuals with CF. Further evaluation of the cause of resistance and clinical impact of ceftazidime–avibactam in CF patients with MDR P. aeruginosa is warranted.